Phylogeny of the 'orchid-like' bladderworts (gen. Utricularia sect. Orchidioides and Iperua: Lentibulariaceae) with remarks on the stolon-tuber system - Gomes Rodrigues, Fernanda [UNESP]; Franco Marulanda, Néstor [UNESP]; Silva, Saura R. [UNESP]; Płachno, Bartosz J.; Adamec, Lubomír; Miranda, Vitor F. O. [UNESP] (My University, 2017)
•Background and Aims The 'orchid-like' bladderworts (Utricularia) comprise 15 species separated into two sections: Orchidioides and Iperua. These robust and mostly epiphytic species were originally grouped within the section Orchidioides by the first taxonomical systems. These species were later split into two sections when sect. Iperua was proposed. Due to the lack of strong evidence based on a robust phylogenetic perspective, this study presents a phylogenetic proposal based on four different DNA sequences (plastid and nuclear) and morphology to test the monophyly of the two sections. • Methods In comparison with all previous phylogenetic studies, the largest number of species across the sections was covered: 11 species from sections Orchidioides and Iperua with 14 species as an external group. Maximum likelihood and Bayesian inferences were applied to DNA sequences of rps16, trnL-F, matK, the internal transcribed spacer (ITS) and three morphological characters: (1) the crest of the corolla; (2) the primary organs in the embryo; and (3) tubers. Additionally, a histochemical analysis of the stolons and tubers is presented from an evolutionary perspective. • Key Results The analyses showed the paraphyly of sect. Iperua, since Utricularia humboldtii is more related to the clade of sect. Orchidioides. Utricularia cornigera is grouped in the sect. Iperua clade based on chloroplast DNA sequences, but it is nested to sect. Orchidioides according to ITS dataset. Morphological characters do not support the breaking up of the 'orchid-like' species into two sections, either. Moreover, the stolon-tuber systems of both sections serve exclusively for water storage, according to histological analyses. • Conclusions This study provides strong evidence, based on DNA sequences from two genomic compartments (plastid and nucleus) and morphology to group the Utricularia sect. Orchidioides into the sect. Iperua. The tubers are important adaptations for water storage and have been derived from stolons at least twice in the phylogenetic history of 'orchid-like' bladderworts.
Keywords: anatomy; Molecular phylogeny; morphology; section Iperua; section Orchidioides; tuber; Utricularia